(untitled) (Communications in Computational Chemistry, 2025)
Surfaces and interfaces play a critical role in exploring novel chemical and physical properties because the interactions between surface and adsorbents, as well as interfacial interactions, can be finely tuned by the interface configurations at the atomic level across a wide range, from strong covalent and ionic bonds to weak hydrogen bonds and van der Waals interactions. These interactions enable precise control over molecular adsorption, self-assembly, and activation, facilitating the design of nanostructures and modulation of novel properties. Recent developments in computational technologies, including high-throughput screening and machine learning, have significantly accelerated the discovery of functional materials. This review highlights theoretical progress in manipulating the physical and chemical properties of organic molecules at surfaces and interfaces, with a focus on controlling molecular configuration and magnetism, selective activation, on-surface synthesis, and interfacial engineering of 2D materials. Our goal is to understand the key factors influencing the physical and chemical properties at surfaces and interfaces, with a particular focus on theoretical insights and computational approaches.